Implementasi Program Penanggulangan TB Paru dengan Strategi Directly Observed Treatment Shortcourse di Puskesmas Panyabungan Jae Kabupaten Mandailing Natal - Mawaddah Marahmah; Rapotan Hasibuan (Universitas Baiturrahim, 2021)
TB cases in Southeast Asia contribute 40% of the world's TB cases and causes the highest mortality in Indonesia. Panyabungan Jae Health Center (PJHC) itself has the highest number of TB cases in Mandailing Natal Regency. This study, therefore, aimed to determine the implementation of the TB Control Program with the Directly Observed Treatment Shortcourse Strategy (DOTS) at PJHC.Qualitative methods with descriptive approach was used for this research. In-depth interviews was conducted with 5 informants in July 2020. The data were analyzed using data reduction, data presentation, and conclusion drawing.The research found that communication between the TB program officer and the DOTS strategy worked well in the PJHC as well as the disposition, resources and bureaucratic structures. Political commitment in the DOTS strategy with cross-sectoral cooperation has an important influence in the handling of TB cases,however village authorities have not played a role in efforts to reduce for number of TB cases. The patients had lack of understanding about TB and some localshad views TB as a disease caused by poison becomes an obstacle in treating patients. TB prevention with the DOTS strategy at the PJHC runs according to standard guidelines, and complemented by the Puskesmas innovation